Pengembangan Instrumen Soal Berbasis HOTS pada Pelajaran IPA Kelas IV Sekolah Dasar: - Putri, Egathy Enetika; Akbar, M. Taheri; Lara , Sylvia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine how the validity and practicality of the development of Hots-basedquestion instruments in grade IV science lessons in elementary schools. This research uses theDick & Carry model development method. The Dick & Carry model itself is one of the systematiclearning design models and rests on the theoretical foundation of a lesson. The results of this study indicate that the Hots question instrument that has been produced in this study is categorized as very valid. In this study, the validity value of the media, material, and language aspects was 93.18%, 92.5%, and 90%, respectively. In addition, the Hots question instrument that has been produced has a very good practicality to be used in the learning process. From the results ofvalidity and practicality, it can be concluded that the Hots question instrument developed is validand practical.